Emerging Concepts in Dyadic Research. (17th December 2021) - Lyons, Karen; Rauer, Amy
Abstract: This session includes four papers that explore and expand upon emerging concepts in dyadic research in health, illness, and end-of-life. First, Dr. Karen Lyons and colleagues examine the concept of dyadic mental health in mid-late life couples living with lung cancer. The paper examines the impact of having optimal versus poor dyadic mental health at diagnosis on the physical health of the couple over time, but also explores the ways we examine the concept of dyadic health in research and potential implications of these methods. Second, Dr. Lyndsey Miller and colleagues take a dyadic approach to understanding the roles of social activity and connectedness on depressive symptoms in a sample of community-dwelling older couples. The paper not only highlights important gender differences, but also the salient role of incongruent dyadic physical health. Third, Dr. Ranak Trivedi and colleagues describe the findings of a novel pilot intervention targeted at improving dyadic self-management in care dyads where one member is a Veteran with chronic conditions. The paper draws upon concepts of collaboration and dyadic coping to conceptualize self-management as a dyadic phenomenon. Finally, Dr. Buck and colleagues explore the novel concept of dyadic dissolution in a sample of family caregivers after the death of their care partner. The paper explores the concept as a cognitive and affective process with implications for how the surviving partner adapts over time. Speakers and Discussant, Dr. Amy Rauer, will focus on implications of these concepts for advancing dyadic science of health and illness across the lifespan.